Cost-effectiveness of a Digital Health Intervention for Acute Myocardial Infarction Recovery. Issue 11 (November 2021) - Bhardwaj, Vinayak; Spaulding, Erin M.; Marvel, Francoise A.; LaFave, Sarah; Yu, Jeffrey; Mota, Daniel; Lorigiano, Ting-Jia; Huynh, Pauline P.; Shan, Rongzi; Yesantharao, Pooja S.; Lee, Matthias A.; Yang, William E.; et al.
Abstract : Background: Acute myocardial infarction (AMI) is a common cause of hospital admissions, readmissions, and mortality worldwide. Digital health interventions (DHIs) that promote self-management, adherence to guideline-directed therapy, and cardiovascular risk reduction may improve health outcomes in this population. The "Corrie" DHI consists of a smartphone application, smartwatch, and wireless blood pressure monitor to support medication tracking, education, vital signs monitoring, and care coordination. We aimed to assess the cost-effectiveness of this DHI plus standard of care in reducing 30-day readmissions among AMI patients in comparison to standard of care alone. Methods: A Markov model was used to explore cost-effectiveness from the hospital perspective. The time horizon of the analysis was 1 year, with 30-day cycles, using inflation-adjusted cost data with no discount rate. Currencies were quantified in US dollars, and effectiveness was measured in quality-adjusted life-years (QALYs). The results were interpreted as an incremental cost-effectiveness ratio at a threshold of $100, 000 per QALY. Univariate sensitivity and multivariate probabilistic sensitivity analyses tested model uncertainty. Results: The DHI reduced costs and increased QALYs on average, dominating standard of care in 99.7% of simulations in the probabilistic analysis. Based on the assumption that the DHI costs $2750 per patient, use of the DHI leads to a cost-savings of $7274 per patient compared with standard of care alone. Conclusions: Our results demonstrate that this DHI is cost-saving through the reduction of risk for all-cause readmission following AMI. DHIs that promote improved adherence with guideline-based health care can reduce hospital readmissions and associated costs. Abstract : Supplemental Digital Content is available in the text.